Nuevas formas de producción textual. El desarrollo de la web - Alonso González, Enrique (ENDOXA, 2007)
The current techniques to produce texts and documents have inherited largely die devised models to work with oíd typewriters. Nevertheless, it has been progressively appraised the possibility of considering new techniques to produce texts impelled by the development of a Wold Wide Web based on documents written in HTML. Tagged texts and Mark-up languages have shown the existence of new strategies to interact with artificial agents far beyond the traditional goals posed by Artificial Intelligence. At the present time the main task consists in designing efficient text processors oriented to compose tagged. The new strategies can produce a true revolution in the textual production techniques.